MODEL OF THE MUTUAL INFLUENCE OF ENVIRONMENTAL ASPECTS AND ENERGY RATIONING ON TRAIN TRACTION IN RAILWAY LOGISTICS (Transport systems and technologies, 2021)
The article deals with the issues of environmental taxation of carbon dioxide emissions by the countries of the European Union and the methodology for calculating the amount of emissions by regulatory documents of Ukraine. It is established that our country's methodology is not adapted to real operating conditions under the influence of cross-border carbon taxation and the "Emissions Trading System". A mathematical model of the impact of power generating stations of states and their contribution to the overall energy balance of the country on the environmental cost and mass emissions of 1 kWh of electricity generation is proposed. The amount of electricity losses during its transportation from the power plant to the electric moving warehouse is determined and is taken into account in the total amount of deductions for the "Emissions Trading System" for DC and AC railway networks. Schemes of transit and local cargo routes are considered on the basis of a real fleet of traction rolling stock of Railways and a network of logistics lines. The passport characteristics of locomotives are analyzed and the amount of emissions and deductions during operation at Rated mode and idle speed is determined. Specific norms for selected routes and train conditions are calculated. The total costs, their cost and the amount of emissions and taxation of selected routes are determined, and rational economic and environmental logistics lines of train traffic are determined on their basis.
Keywords: cost rationing, carbon dioxide emissions, energy resources, mathematical modeling, traction rolling stock, environmental indicators, transportation logistics.